Some thoughts on the possible health effects of electric and magnetic fields and exposure guidelines - Barnes, Frank; Freeman, Jr Eugene R. (Frontiers in Public Health, 2022)
Concerns about the possible health effects from exposure to weak electric and magnetic (EM) fields have been debated since the early 1960s. It is now well established that biological systems respond to exposure to weak EM fields at energy levels well below the current safety guidelines which result in modification of their functionality without significant changes in temperature. These observations are adding to the debate over what should be done to protect the users of cellular telecommunications systems. Experimental results showing both increases and decreases in cancer cell growth rates and concentration of reactive oxygen species for exposure to nano-Tesla magnetic fields at both radio frequencies (RF) and extra low frequencies (ELF) are cited in this paper. Some theoretical models on how variations in EM exposure can lead to different biological outcomes and how feedback and repair processes often mitigate potential health effects due to long-term exposure to low-level EM energy sources are presented. Of particular interest are the application of the radical pair mechanisms that affect polarization of electrons, and nuclear spins and the importance of time-delayed feedback loops and the timing of perturbations to oscillations in biological systems. These models help account for some of the apparently conflicting experimental results reported and suggest further investigation. These observations are discussed with particular emphasis on setting future safety guidelines for exposure to electromagnetic fields in cellular telecommunications systems. The papers cited are a very small fraction of those in the literature showing both biological effects and no effects from weak electric and magnetic fields.